Specific phosphorylation of microtubule-associated protein 2c by extracellular signal-regulated kinase reduces interactions at its Pro-rich regions - Plucarová, Jitka; Jansen, Séverine; Narasimhan, Subhash; Laníková, Alice; Lewitzky, Marc; Feller, Stephan M; Žídek, Lukáš (The Journal of biological chemistry, 2022)
Microtubule-associated protein 2 (MAP2) is an important neuronal target of extracellular signal-regulated kinase 2 (ERK2) involved in Raf signaling pathways, but mechanistic details of MAP2 phosphorylation are unclear. Here, we used NMR spectroscopy to quantitatively describe the kinetics of phosphorylation of individual serines and threonines in the embryonic MAP2 variant MAP2c. We carried out real-time monitoring of phosphorylation to discover major phosphorylation sites that were not identified in previous studies relying on specific antibodies. Our comparison with the phosphorylation of MAP2c by a model cyclin-dependent kinase CDK2 and with phosphorylation of the MAP2c homolog Tau revealed differences in phosphorylation profiles that explain specificity of regulation of biological functions of MAP2c and Tau. To probe the molecular basis of the regulatory effect of ERK2, we investigated the interactions of phosphorylated and unphosphorylated MAP2c by NMR with single-residue resolution. As ERK2 phosphorylates mostly outside the regions binding microtubules, we studied the binding of proteins other than tubulin, namely regulatory subunit RIIα of cAMP-dependent PKA, adapter protein Grb2, Src homology domain 3 of tyrosine kinases Fyn and Abl, and ERK2 itself. We found ERK2 phosphorylation interfered mostly with binding to proline-rich regions of MAP2c. Furthermore, our NMR experiments in SH-SY5Y neuroblastoma cell lysates showed that the kinetics of dephosphorylation are compatible with in-cell NMR studies and that residues targeted by ERK2 and PKA are efficiently phosphorylated in the cell lysates. Taken together, our results provide a deeper characterization of MAP2c phosphorylation and its effects on interactions with other proteins.
Keywords: Proline-Directed Protein Kinases; mikrotubuly; proteinkinasy řízené prolinem; Cell Line, Tumor; Src homology 3 domain; nádorové buněčné linie; lidé; cyclin-dependent kinase; NMR; microtubule-associated protein; Humans; extracellular signal–regulated kinase; proteiny asociované s mikrotubuly; growth factor receptor-bound protein 2 (GRB2); fosforylace; Microtubules; Microtubule-Associated Proteins; PKA; extracelulárním signálem regulované MAP kinasy; Phosphorylation; Extracellular Signal-Regulated MAP Kinases